Recurring victimization: What role does head injury play?. (September 2018) - Daigle, Leah E.; Harris, Michelle N.
Abstract: Purpose: There is little understanding of why some victims experience multiple victimization events while others are victimized once or not at all. One possible distinguishing characteristic is having a prior head injury, given the strong linkage between prior head injuries and aggression/violence and their connection to victimization. It is plausible that prior head injuries may also lead to recurring victimization. Methods: To examine the possibility that head injury and serious head injury may distinguish between people who are non-victims, single-wave victims, or recurring-victims, we use data from multiple waves of the Pathways to Desistance study. Multinomial regression analyses were utilized to examine prior head injury's (and serious head injury's) effects on being a recurring victim compared to a single-wave victim or non-victim, holding constant demographic controls and other related correlates that may be related to head injury and victimization status. Results: We find that having a prior head injury and serious head injury are able to distinguish between non-victims, single-wave victims, and recurring-victims. Conclusions: Head injury increases the odds of being a recurring victim compared to a non-victim, and serious head injury increases the odds of being a recurring victim compared to a non-victim and a single-wave victim. Future research, theoretical implications, and policy implications are discussed. Highlights: Head injury is more common among recurring victims than others Head injury increases the odds of being a recurring victim compared to a non-victim Head injury increases the odds of being a recurring victim compared to a single-wave victim Serious Head injury increases the odds of being a recurring victim compared to a non-victim Serious Head injury increases the odds of being a recurring victim compared to a single-wave victim